Методичні підходи до обліку операцій з надходження необоротних активів - Кафка, С. М.; Степанюк, О. С. (Видавництво Львівської політехніки, 2014)
Розглянуто економічне трактування поняття “надходження” в науковій літературі, що дало змогу систематизувати основні шляхи надходження необоротних активів на підприємство, критерії їх визнання та відображення таких операцій в бухгалтерському обліку, розкрито методичні підходи до формування первісної вартості необоротних активів у різних країнах Європи та у вітчизняній практиці. The economic interpretation of the notion “income” in the scientific literature has been considered that has made it possible to systematize the main ways of non-current-assets revenues to the company. For this purpose the analysis of scientific publications related to the revenue fixed assets in Ukraine for 2011-2013 has been carried out and two issues discussed by scientists have been singled out: an accounting reflection of revenue fixed- assets transactions and their tax issues. It should be indicated that there is some difference in the interpretation of the “revenue non-current assets” concept in domestic regulations. In general, the company needs providing with constant updating of fixed assets for production efficiency. The main proposals and recommendations to improve accounting of revenue fixed assets (non-current assets) have been found in the course of investigation. Fixed assets can be delivered to the company in different ways: namely they can be created on their own or as a result of obtaining from legal or natural persons. The received fixed assets are included in the enterprise balance sheet at their first cost. The first cost of such fixed assets depends on the fact by what means the non-current assets object has been received.. The methodical approaches to the formation of the original value of fixed assets in different countries of Europe have been revealed and the current national practice included.
Methodological approaches to accounting operations revenues non-current assets
Keywords: бухгалтерський облік; необоротні активи; основні засоби; обмінні операції; вартість; стандарти; облікові регламентації; методика; accounting; fixed assets; foreign operations; cost; standards; accounting regulations; methods